(untitled) (Gestão & Regionalidade, 2023)
The goal of this study was to analyze the materialization of collaborative governance in the context of coping with the covid-19 pandemic in a municipally in Rio Grande do Sul, from the perception of government, companies, university and civil society helixes. Interviews were carried out with representatives of each helix and consultation of municipal decrees regarding measures to protect against covid-19. The Content Analysis technique was used. The actions to face the pandemic were taken by the Executive Power within the scope of the Comitê de Enfrentamento do Novo Coronavírus, which had the participation of representatives from various segments of the public and private sector. It cannot be said that collaborative governance was implemented, as there was no integrated action of all the helixes in the search for consensus in the management of the pandemic, with emphasis on the dissatisfaction of the companies with the measures adopted by the government.